Efficient use of jute agro textiles as soil conditioner to increase chilli productivity on Inceptisol of West Bengal - ADHIKARI, NABANITA; DISHA, ARIF; MAHATA, ANGIRA PRASAD; PAL, ARUNABHA; ADHIKARI, RAHUL; SARDAR, MILAN; SAHA, ANANYA; BAURI, SANJIB KUMAR; TARAFDAR, P. K.; DE, SUSANTA KUMAR (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted at the University farm of Regional Research Station, New Alluvial zone of Bidhan Chandra Krishi Viswavidyalaya, Gayespur under Nadia district of West Bengal which is situated at 220 58’ 31’’ N L, 880 26’ 20’’ E L, with an altitude at 10.9 m above the mean sea level to investigate the effect of various strength (gram per meter square) of jute agro textiles on change of soil properties on chilli yield. Five treatment combinations viz. T1 - farmers practices (control), T2 - 200 GSM jute agro textiles, T3- 400 GSM jute agro textiles, T4 - 600 GSM jute agro textiles and T5- 800 GSM jute agro textiles were spread before transplanting of chilli seedlings along with the levels of N-P-K at 50-25-25 kg/ ha and in RBD design with four réplications. Initials and final soil samples were analyzed for relevant physical and chemical properties by following standard methods. The yields of crop were found 10.00, 16.26, 17.57, 14.02 and 12.00t/ha respectively in T1, T2, T3. T4 and T5. The yield of crop was increased 7.57t/ha (75.7%) under 400 GSM jute agro textiles over – farmers practices (control). The result showed the decreased bulk density and increased porosity under all treatments. They also improved moisture use efficiency, in general, by 96.5% over control. Decreasing bulk density with simultaneous increasing of porosity under jute agro textile treatments also improved the moisture retention capacity in soil. Better aggregation and their stabilization as well as chilli yield occurred with applied T3 - 400 GSM jute agro textiles treatments.